Does History Conquer Love? The Good of the Family and the Gift of Self - López, Antonio (Socialinė teorija, empirija, politika ir praktika, 2017)
The aim of this article is to show how the modern liberal view of marriage as a temporary association contracted by two equal and autonomous individuals overrides and obscures an essential anthropological truth of the human person. Specifically, a reduction of marriage to the level of a purely historical good results in the obfuscation of the gift-like character of human existence and in the subordination of nuptial love to a mere “means” in service of some extrinsic, impersonal goal. Only a more robust anthropological vision, informed by categories of man’s filial and nuptial existence, is able to secure a historical order that can be a genuine “end” of indefatigable love unto itself. Only by attending to the paradoxical character of God creating man in his image as “male” and “female” does history avoid becoming an order of mere chronological or biological succession, and only thus does the rationale and gratuitousness of an indissoluble sacrament of marriage come to be seen as indispensable for preserving and promoting the dignity of historical man